Sabour Tisi-1: High yielding linseed variety (Linum usitatissimum L.) for utera condition suitable for north eastern zone of India: SABOUR TISI-1: HIGH YIELDING LINSEED VARIETY FOR UTERA CONDITION FOR NORTH EASTERN INDIA - RAM BALAK PRASAD NIRALA; SHIVASANKAR ACHARYA; AMARENDRA KUMAR (Journal of Oilseeds Research, 2019)
A pure line variety, Sabour Tisi-1 (BAUP 101) was developed and evaluated in AICRP on linseed trials from 2013-14 to 2015-16. Average seed yield of Sabour Tisi-1 (BAUP101) was 686 kg per ha, which was 27.75% and 142.40% higher yield than the national check, T397 and zonal check, R552, respectively. Similarly, the oil yield was 196 kg per ha which was 20.25% and 80.46% higher oil yield than the national check (T397) and zonal check (R552) respectively. Varietal Identification Committee of ICAR identified Sabour Tisi-1 (BAUP 101) in 2016 for utera condition of zone II ofIndia comprising the states ofBihar, Jharkhand, West Bengal, Assamand Uttar Pradesh excluding Bundelkhand. This variety has been recommended for release and notification (Central Varieties) by Central Sub-Committee on Crop Standards, notification and release of varieties for agricultural Crops, Government of India, Ministry of Agriculture and Farmers Welfare and published in the Gazette of India.